Fiscal Aspects of Bank Restructuring - Daniel, James (Washington, D.C. : International Monetary Fund, 1997)
Governments frequently assist troubled banks. This paper examines the fiscal aspects of such assistance: rationale, design criteria, methods, and macroeconomic implications. It concludes that (1) banks should be assisted only when there is a clear systemic risk; (2) assistance should be tied to a comprehensive restructuring program, minimize fiscal cost, be equitable and transparent, prevent recurrence, and facilitate a sound macroeconomic environment; (3) debt-based assistance will worsen public sector debt sustainability and will probably increase aggregate demand; and (4) assistance may require a substantial fiscal response (especially given the possible need for a looser monetary stance), which should feed iteratively into the choice of restructuring strategy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet